Strategy for endovascular treatment of a patient with combined coronary and carotid artery atherosclerosis: a case report - F. B. Shukurov; B. А. Rudenko; D. A. Feshchenko; D. K. Vasiliev; M. T. Taliuridze (Кардиоваскулярная терапия и профилактика)
Treatment of patients with combined coronary and carotid artery atherosclerosis is a difficult task due to the increased risk of surgical intervention in this cohort of patients. Lack of timely treatment can lead to a decrease in the quality of life of patients, as well as to death. In some cases with combined coronary and carotid artery atherosclerosis, the choice of surgical intervention may depend on vascular bed involvement. In a case report, open surgery was associated with a very high risk of perioperative complications; so the only way of myocardial revascularization was minimally invasive endovascular surgery. The article presents a case of the treatment of a patient with a combined multivessel coronary and bilateral carotid artery atherosclerosis.